SBP-Program

f

tw

in

Dividing unlike monomials

How to divide unlike monomials? How do you divide unlike monomials?

Examples of dividing unlike monomials

Dividing monomials example.

Divide the monomials

12ab / (6b)

Solution.

12ab / (6b) =
(12 / 6) * (ab / b) =
(2) * (a) =
2a

The answer: 2a.

Example of dividing monomials.

Dividing monomials

8ab2 / (2b)

Solution.

8ab2 / (2b) =
(8 / 2) * (ab2 / b1) =
(4) * ab2 - 1) =
4ab1 = 4ab

The answer: 4ab.

Example of dividing monomials.

Divide the following monomials

7.6a4 / (2a2)

Solution.

7.6a4 / (2a2) =
(7.6 / 2) * (a4 / a2) =
(3.8) * (a4 - 2) =
3.8a2

The answer: 3.8a2.

Example of dividing monomials.

Divide the monomials

18a2 / (2a-5)

Solution.

18a2 / (2a-5) =
(18 / 2) * (a2 / a-5) =
(9) * (a2 - (-5)) =
9a7

The answer: 9a7.